Awareness and Availment of Benefits of Senior Citizens in A Highly Urbanized City - Gerolin, Louieze Gerald C.; Palic, Anabelle S. (Philippine Social Science Journal, 2020)
Republic Act (RA) 9994, otherwise known as the Expanded Senior Citizen Act of 2010, was enacted into law to provide more benefits to the elderly and deliver full support to their well-being (Inabangan et al., 2019). The benefits are essential as most of them no longer hold jobs, and financial stability can be challenging if not fatal. The current laws and policy provisions on food and medicine discount and the granting of a social pension to underprivileged senior citizens are only palliatives at best. However, they stretch the limited incomes of these individuals and their supporting families who live below the poverty level. The purpose of the study is to assess the level of awareness and extent of availment on the benefits under RA 9994 of senior citizens in a highly urbanized city of Negros Occidental as well as the relationship between awareness and availment. Likewise, explore the challenges encountered by senior citizens in availing their benefits under RA 9994.